UPAYA GURU MENINGKATKAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN JIGSAW PADA MATA PELAJARAN FIQIH KELAS VII SMP IT INSAN MANDIRI BANDAR LAMPUNG - Muhammad Marsal Kamil; Subandi; Baharuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low learning outcomes of the Fiqh of Prayer of seventh grade students of SMP IT Insan Mandiri Bandar Lampung indicate the need for learning innovations that can encourage student activity and comprehensive understanding. This study aims to analyze teachers' efforts in improving Fiqh learning outcomes through the implementation of the Jigsaw cooperative learning model. The study used a qualitative approach with the Classroom Action Research (CAR) method which was implemented in two cycles, including the planning, implementation, observation, and reflection stages, with 28 students as research subjects. The results showed that the implementation of the Jigsaw model was able to significantly improve the quality of the learning process and student learning outcomes. Teachers' teaching activities increased from 66.67% in cycle I to 90.48% in cycle II, while students' learning activities increased from 61.14% to 80.95%. This increase has an impact on student learning outcomes, marked by an increase in learning completeness from 60.71% in cycle I to 89.29% in cycle II, with the average score increasing from 64 to 83 and exceeding the Minimum Completion Criteria (KKM) of 75. The findings of this study indicate that the Jigsaw cooperative learning model is effective in increasing activeness, cooperation, learning responsibility, and understanding of the concept of Fiqh Salat. The implications of this study provide practical contributions for teachers in developing participatory and meaningful Fiqh learning, as well as being a reference for schools in implementing innovative learning models based on Islamic values.